Innovative protein sources for sustainable sheep farming: Assesing black soldier fly larvae meal in merino lamb diet - Odeon, Maria Mercedes; Fernandez Arhex, Valeria Cristina; Garcia Falabella, Brenda Marilyn; Villar, Maria Laura; Caballero, Veronica Jorgelina; Hara, Sofia Maria; Cancino, Andrea Karina; Villagra, Edgar Sebastian (Elsevier, 2025)
The growing global demand for animal-based food poses challenges to sustainability and animal welfare, especially in intensive production systems. This study explores the potential of black soldier fly larvae (BSFL) meal as a sustainable and innovative protein source for Merino lamb diets, offering an alternative to soybean expeller meal. Over a 50-day fattening period, Merino lambs were fed two dietary treatments: soybean expeller meal (S) and BSFL meal. Key metrics were evaluated, including productive performance (body weight, body condition score, feed intake, average daily gain, and feed conversion efficiency), ruminal fermentation profiles, and some stress biochemical indicators (glucose levels, cortisol levels, and plasma protein concentrations). Notably, no significant differences were found between diets in terms of growth performance, ruminal health, or stress markers, suggesting that BSFL meal could be a viable and competitive alternative. These results highlight the potential of BSFL to enhance sustainability in small ruminant production by reducing reliance on environmentally impactful feed ingredients like soybean expeller meal. This study underscores the relevance of BSFL meal in promoting resource efficiency, environmental conservation, and innovative solutions in small ruminant nutrition. These findings open the door to the inclusion of insect use, specifically black soldier fly larvae, in ruminant diets as a viable strategy to improve the sustainability of production systems.